ПРОГРАМИ РОЗВИТКУ ШВИДКІСНО-СИЛОВИХ ЯКОСТЕЙ БОРЦІВ - Палічук, Юрій; Shukatka, Oksana; Мартинів, Олег; Вілігорський, Олександр (Імідж сучасного педагога, 2020)
апропонована програма розвитку швидкісно-силових якостей борців забезпечила достовірне зростання значень анаероб-ного компоненту спеціальної витривалості, збільшення її швидкісно-силового та силового компонентів за результатами тестів у присіданні з партнером своєї ваги та підтягування на перекладині.Результатом упровадженої програми тренувань було покращення змагальної діяльності, що підтверджувалося вірогідним зростанням тривалості реальних атак, зменшенням часу інтервалів між атаками, збільшенням часу успішних атак і збільшенням часу поєдинку загалом. Як наслідок – зросла загальна кількість перемог на фоні незмінного числа поразок.
Programs of development of speed and strength qualities of wrestlers
The proposed program for the development of speed-strength qualities of wrestlers at the stage of preliminary basic training provided a reliable increase in the values of the anaerobic component of special endurance, increase in its strength and speed-strength components according to the results of tests in a squat with a partner of your weight and pulling with a jerk on the bar. The result of the implemented training program was an improvement in competitive activity, which was confirmed by the likely increase in the duration of real attacks, a decrease in the time intervals between attacks, an increase in the time of successful attacks, and an increase in the time of the fight as a whole. As a result, the total number of victories increased against the background of a constant number of defeats. Material and methods: Analysis of scientific and specialized literature; pedagogical observation and experiment; pedagogical testing (a comprehensive assessment of speed-strength fitness of wrestlers at the stage of preliminary basic training based on an analysis of their physical fitness level according to special endurance indicators, based on a study of speed-strength qualities and a study of the effectiveness of competitive activity); methods of mathematical statistics. Speed-strength and special speed-strength training are the main components of athlete’s physical fitness. The effectiveness of techniques and the success of performances in competitions depend on the level of development of speed- strength qualities. A special place in the sports training of wrestlers is occupied by the methods of speed- strength stresses and speed-strength movements, and the researchers recommend using the short-effort method for this purpose - overcoming maximum resistance with creating a physiological stimulus of maximum strength.
Keywords: боротьба; програма; ефективність; швидкісно-силові якості; підготовка; wrestling; program; efficiency; speed-strength qualities; training